Do males pay for sex? Sex‐specific selection coefficients suggest not. (31st January 2017) - Prokop, Zofia M.; Prus, Monika A.; Gaczorek, Tomasz S.; Sychta, Karolina; Palka, Joanna K.; Plesnar‐Bielak, Agata; Skarboń, Magdalena
Abstract : Selection acting on males can reduce mutation load of sexual relative to asexual populations, thus mitigating the twofold cost of sex, provided that it seeks and destroys the same mutations as selection acting on females, but with higher efficiency. This could happen due to sexual selection—a potent evolutionary force that in most systems predominantly affects males. We used replicate populations of red flour beetles ( Tribolium castaneum ) to study sex‐specific selection against deleterious mutations introduced with ionizing radiation. We found no evidence for selection being stronger in males than in females; in fact, we observed a nonsignificant trend in the opposite direction. This suggests that selection on males does not reduce mutation load below the level expected under the (hypothetical) scenario of asexual reproduction. Additionally, we employed a novel approach, based on a simple model, to quantify the relative contributions of sexual and offspring viability selection to the overall selection observed in males. We found them to be similar in magnitude; however, only the offspring viability component was statistically significant. In summary, we found no support for the hypothesis that selection on males in general, and sexual selection in particular, contributes to the evolutionary maintenance of sex.